Julio Ángel Olivares Merino, Jaume Balagueró: en nombre de la oscuridad, Akal, Madrid, 2011. ISBN 978-84-460-2919-9. - Laura Blázquez Cruz (Universitat Autònoma de Barcelona, 2020)
Julio Ángel Olivares Merino, Jaume Balagueró: en nombre de la oscuridad, Akal, Madrid, 2011. ISBN 978-84-460-2919-9.